Telerehabilitation with Tablet Computers Replaces Face-to-Face Rehabilitation. (2nd January 2020) - Wakasa, Masahiko; Odashima, Tsubasa; Saito, Akira; Kimoto, Minoru; Saito, Isao; Handa, Shogo; Syukunobe, Kazuki; Kume, Yu; Okada, Kyoji
Abstract: Aims : The objective of this study was to introduce mobile telerehabilitation with tablet computers and to verify its practical effectiveness in improving physical function and health status. Methods : In this study, nine adults aged 76.3 ± 3.3 years old participated in 13 exercise sessions led by a physical therapist each lasting 60 min every 2 weeks for a total of 6 months. A physical therapist performed exercises in front of a digital camera which was connected to a lab computer. In a community center, participants performed the exercises while watching the exercise performance on a screen. Intervention was delivered by video conferencing over high-speed mobile Internet. Results : All participants were satisfied with telerehabilitation. We found that patients experienced significant improvement in physical function following participation. Conclusion : Mobile telerehabilitation provides an alternative option for delivering physical exercise and supervision, especially for those with geographical restrictions and limited local professional resources.